Prognostic Value of The Lactate/Albumin Ratio for Predicting 28-Day Mortality in Critically ILL Sepsis Patients. Issue 5 (November 2018) - Shin, Jikyoung; Hwang, Sung Yeon; Jo, Ik Joon; Kim, Won Young; Ryoo, Seung Mok; Kang, Gu Hyun; Kim, Kyuseok; Jo, You Hwan; Chung, Sung Phil; Joo, Young Seon; Beom, Jin Ho; Yoon, Young Hoon; et al.
ABSTRACT: Aim: The aim of this study was to evaluate the clinical utility of the lactate/albumin (L/A) ratio as a predictive factor of 28-day mortality in critically ill sepsis patients. Methods: This is a retrospective observational study from a prospectively collected multicenter registry of 10 emergency departments (EDs) in teaching hospitals that participated in the Korean Shock Society. It enrolled patients who were 19 years of age or older who had a suspected or confirmed infection and evidence of refractory hypotension or hypoperfusion. The prognostic performance of the L/A ratio and lactate level for predicting 28-day mortality was assessed. Lactate and albumin levels were measured immediately after ED arrival. Results: A total of 946 patients were included, with 22.5% overall 28-day mortality. The area under the receiver operating characteristic curve (AUROC) value of the L/A ratio (0.69, 95% confidence interval [CI] 0.64–0.73, P  < 0.01) was higher than that of lactate (0.65, 95% CI 0.61–0.70, P  < 0.01) for predicting 28-day mortality. The optimal cutoff of the L/A ratio was 1.32. The AUROC value of the L/A ratio was better than that of lactate regardless of lactate level (normal [<2.0 mmol/L]: 0.68 vs. 0.55; intermediate [≥2.0,  < 4.0 mmol/L]: 0.65 vs. 0.50; high [≥4.0 mmol/L]: 0.66 vs. 0.62). In the subgroup with decreased lactate elimination, the AUROC value of the L/A ratio was also significantly higher than that of lactate (hepatic dysfunction: 0.70 vs. 0.66; renal dysfunction: 0.71 vs. 0.67). The L/A ratio cut-off and hypoalbminemia showed further discriminative value for 28-day mortality even in patients with normal or intermediate lactate levels. Conclusions: The prognostic performance of the L/A ratio was superior to that of a single lactate measurement for predicting 28-day mortality of critically ill sepsis patients. L/A ratio can be a useful prognostic factor regardless of initial lactate level and the presence of hepatic or renal dysfunction.